Knowledge, attitude and practice on elder maltreatment among staff in the aged care institution - Mansor, Mariani; Ismail, Nurhilmiyani; Shariff Ghazali, Sazlina; Tengku Abdul Hamid, Tengku Aizan; Md Noor, Amna (Universiti Putra Malaysia Press, 2019)
Elder maltreatment or abuse is an important issue to be addressed, especially in institutional care settings where most of the elders are vulnerable and dependent on others for their daily activities. With a rapidly growing older population and increasing rate of chronic and degenerative diseases, long term care system will be on high demand. Research suggests that staff's knowledge and attitude condoning elder abuse are the possible risk factor for executing abusive behaviors against residents in the institutions but have been studied infrequently. Hence, this paper focuses on the prevalence of elder maltreatment in aged care institutions in Selangor. Staff's knowledge, attitude and practice towards elder maltreatment in the aged care institution are discussed. This descriptive study utilized simple random sampling method to identify 110 care workers from 31 public and private aged care institutions in Selangor. Findings showed that majority of the respondents had a low level of knowledge concerning the management of elder maltreatment in a residential setting (M=16.3; SD=8.1), while more than two third (71.8%) were reported to have low level of positive attitude against elder maltreatment. Results also highlighted that majority of the respondents (90.9%) reflected an 'abusive' behavior towards elderly resident at least once during the past 6 months where the physical and psychological maltreatment related to caring activities were most common among them. Taking into account that demographic ageing is taking shape in Malaysia, more attention should be given on education and support towards institutional aged care setting as the primary preventive strategy.